Hypertonic saline improves the LCI in paediatric patients with CF with normal lung function. Issue 5 (30th April 2010) - Amin, Reshma; Subbarao, Padmaja; Jabar, Alisha; Balkovec, Susan; Jensen, Renee; Kerrigan, Shawn; Gustafsson, Per; Ratjen, Felix
Abstract : Background and aims: Sensitive outcome measures to assess the efficacy of therapeutic interventions in patients with cystic fibrosis (CF) with mild lung disease are currently lacking. Our objective was to study the ability of the lung clearance index (LCI), a measure of ventilation inhomogeneity, to detect a treatment response to hypertonic saline inhalation in paediatric patients with CF with normal spirometry. Methods: In a crossover trial, 20 patients with CF received 4 weeks of hypertonic saline (HS) and isotonic saline (IS) in a randomised sequence separated by a 4 week washout period. The primary end point was the change in the LCI due to HS versus IS. Results: Baseline characteristics including the LCI were not significantly different between both study periods. Four weeks of twice-daily HS inhalation significantly improved the LCI compared with IS (1.16, 95% CI 0.26 to 2.05; p=0.016), whereas other outcome measures such as spirometry and quality of life failed to reach statistical significance. Randomisation order had no significant impact on the treatment effect. Conclusions: The LCI, but not spirometry was able to detect a treatment effect from HS inhalation in patients with CF with mild disease and may be a suitable tool to assess early intervention strategies in this patient population. Clinical trial number: NCT00635141.